Programa De Atención E Intervención Psicosocial Desde El Metapropósito Construcción De Habilidades Psicosociales Para La Vida Desde La Gestión Del Bienestar: Fortalecimiento De Las Relaciones Y Proyecto De Vida En Un Grupo De Niños, Niñas Y Adolescentes Del Barrio Tuna Baja En Suba, Bogotá (2022)
The town of Suba is characterized for being one of the largest and most populated towns of Bogotá, where multiple dynamics converge such as intrafamily violence, sale and consumption of psychoactive substances, common crime, among others, which revolve and influence around the theme of childhood and adolescence, which is why the the need to promote and guarantee the rights of children and adolescents for the sake to contribute to their evolution and development, their capabilities and the opportunities they have as agents of their own development